Perilaku Social Loafing pada Mahasiswa Pendidikan Agama Islam : Individualisme Gen-Z di Era Media Sosial - Rosikhan Nabila; Adika Hary Hermawan; Hanim Nofirda Amalia (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Nowadays, Students are the parts of z generation also the agents of change. But, in this social media era there are many deviant behavior. This study aims to describe the social loafing behavior that occurs in Islamic Religious Education (PAI) students based on its aspects. This research uses descriptive qualitative research. Data collection in this study was in the form of questionnaires, interviews, and documentation. Meanwhile, the sample is the active students of the Islamic Religious Education (PAI) study program in semesters 2, 4 and 6 of 2021/2022 as z generation. Based on the result of this research, it is known that social media creates an individualism in z-generation. It made social loafing in Islamic Religious Education (PAI) Students